2022
DOI: 10.3390/nu14193915
|View full text |Cite
|
Sign up to set email alerts
|

Joint Associations of Food Groups with All-Cause and Cause-Specific Mortality in the Mr. OS and Ms. OS Study: A Prospective Cohort

Abstract: Despite continuous growth in dietary pattern research, the relative importance of each dietary component in the overall pattern and their joint effects on mortality risk have not been examined adequately. We explored the individual and joint associations of multiple food groups with all-cause and cause-specific mortality (cardiovascular disease (CVD) or cancer), by analyzing data from a cohort of 3995 Hong Kong Chinese older adults in the Mr. Osteoporosis (OS) and Ms. OS Study. Cox proportional hazards models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…After the exclusion of 2851 duplicate records and 5716 irrelevant documents based on title and abstract screening, 216 potentially relevant full-text articles were considered for further review. After further exclusions were made, 32 prospective cohorts (31 publications) were included in the analyses [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [34] , [35] , [36] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. Of the 31 articles, 1 included data from 2 cohort studies [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the exclusion of 2851 duplicate records and 5716 irrelevant documents based on title and abstract screening, 216 potentially relevant full-text articles were considered for further review. After further exclusions were made, 32 prospective cohorts (31 publications) were included in the analyses [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [34] , [35] , [36] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. Of the 31 articles, 1 included data from 2 cohort studies [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…All were population-based cohort studies that were conducted in the general adult population, and studies in patients with a history of disease were excluded. Five studies were conducted in the United States [ 29 , 40 , 43 , 44 , 61 ], 14 in Europe [ 26 , 30 , 31 , 34 , 35 , 39 , 41 , [64] , [65] , [66] , [67] , [68] , [69] , [70] ], 10 in Asia [ 23 , 24 , 27 , 28 , 36 , 38 , 42 , 45 , 63 ], 1 in Australia [ 62 ], and 2 internationally [ 22 , 25 ]. These studies enrolled 1,141,793 participants, ranging from 161 to 258,911.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chen et al [ 105 ] estimated a summary RRs for high (5+ servings/week) compared with low nut (never/almost never) consumption of 0.87 (95% CI: 0.80–0.93) for cancer mortality (11 studies 21,353 deaths), while Aune et al reported a summary estimate of 0.83 (95% CI: 0.75–0.92) per 28 g/d for cancer mortality [ 106 ]. When updating the latter analysis by adding results from 6 additional cohort studies that have since been published [ 109 , 110 , 111 , 112 , 113 , 114 ] ( Supplementary Table S1 ), the summary estimate was 0.87 (95% CI: 0.81–0.94, I 2 = 60%, n = 13) per 28 g/d ( Figure 1 A) based on data from 13 cohort studies (12 publications), and there was evidence of nonlinearity ( P nonlinearity = 0.005) with most of the reductions in risk observed with an intake of 15–20 g/day ( Figure 1 B).…”
Section: Tree Nuts Peanuts and Cancermentioning
confidence: 99%
“… Nuts and total cancer mortality, linear ( A ), and nonlinear ( B ) dose-response analysis (updated analysis based on Aune et al) [ 106 , 110 , 111 , 112 , 113 , 114 , 119 , 120 , 121 , 122 , 123 , 124 ]. …”
Section: Tree Nuts Peanuts and Cancermentioning
confidence: 99%